Influenza vaccination during the first 6 months after solid organ transplantation is efficacious and safe. (November 2015) - Pérez-Romero, P.; Bulnes-Ramos, A.; Torre-Cisneros, J.; Gavaldá, J.; Aydillo, T.A.; Moreno, A.; Montejo, M.; Fariñas, M.C.; Carratalá, J.; Muñoz, P.; Blanes, M.; Fortún, J.; et al.
Abstract: Preventing influenza infection early after transplantation is essential, given the disease's high mortality. A multicentre prospective cohort study in adult solid organ transplant recipients (SOTR) receiving the influenza vaccine during four consecutive influenza seasons (2009–2013) was performed to assess the immunogenicity and safety of influenza vaccination in SOTR before and 6 months after transplantation. A total of 798 SOTR, 130 of them vaccinated within 6 months of transplantation and 668 of them vaccinated more than 6 months since transplantation. Seroprotection was similar in both groups: 73.1% vs. 76.5% for A/(H1N1)pdm (p 0.49), 67.5% vs. 74.1% for A/H3N2 (p 0.17) and 84.2% vs. 85.2% for influenza B (p 0.80), respectively. Geometric mean titres after vaccination did not differ among groups: 117.32 (95% confidence interval (CI) 81.52, 168.83) vs. 87.43 (95% CI 72.87, 104.91) for A/(H1N1)pdm, 120.45 (95% CI 82.17, 176.57) vs. 97.86 (95% CI 81.34, 117.44) for A/H3N2 and 143.32 (95% CI 103.46, 198.53) vs. 145.54 (95% CI 122.35, 174.24) for influenza B, respectively. After adjusting for confounding factors, time since transplantation was not associated with response to vaccination. No cases of rejection or severe adverse events were detected in patients vaccinated within the first 6 months after transplantation. In conclusion, influenza vaccination within the first 6 months after transplantation is as safe and immunogenic as vaccination thereafter. Thus, administration of the influenza vaccine can be recommended as soon as 1 month after transplantation.